Extraction of total alkaloids, peimine and peiminine from the flower of Fritillaria thunbergii Miq using supercritical carbon dioxide. (March 2017) - Ruan, Xiao; Cui, Wen-xia; Yang, Li; Li, Zhao-hui; Liu, Ben; Wang, Qiang
Graphical abstract: Highlights: This study demonstrated the potential of F. thunbergii flower to be used for food, medicinal, and nutritional purposes. Central composite design (CCD) with four variables and five levels was employed for optimization of process parameters, and response surface plots were constructed in accordance with a second order polynomial model. Ultra performance liquid chromatography (UPLC) with an Evaporative Light Scattering Detector (ELSD) detector was first used to analyze the extracts of F. thunbergii flower. Optimal condition for all response were standardized. The experiment values were in close agreement with predicated values. Abstract: This study for the first time designed to use supercritical fluid extraction (SFE) to extract total alkaloids, peimine and peiminine from the flower of Fritillaria thunbergii Miq. 2, 2′-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) diammonium salt radical cation scavenging activity (ABTS-RSA) and ferric reducing antioxidant potential (FRAP) assay were selected to evaluate the antioxidant capacity of the extracts. A central composite design (CCD) with four variables (extract time (1.5–3.5) h, temperature (50–70) °C, pressure (15–35) MPa and co-solvent (ethanol: water) ratio (80–100, v/v) %was employed for optimization of process parameters, and response surface plots were constructed in accordance with a second order polynomial model. The highest yields of total alkaloids (2.9 mg/g), peimine (0.7 mg/g) and peiminine (0.07 mg/g) were predicted at optimal conditions of 2.9 h, 61.3 °C, 30.6 MPa and 90.3% ethanol and the antioxidant activity of the extracts was estimated to be comparable to that of α-tocopherol with ABTS value of 0.5 mg/mL and FRAP value of 658 mg AAE/100 g, respectively. These results suggest that optimization of the extraction conditions is critical for accurate quantification of total alkaloids, peimine and peiminine, and antioxidants in F. thunbergii Miq flower, which may further be used for industrial extraction procedure.